Therapeutical strategies in cavitary legionnaires' disease, two cases from the field and a systematic review - Marco Moretti; Lisanne De Boek; Bart Ilsen; Thomas Demuyser; Eef Vanderhelst (BMC, 2023)
Abstract Background Legionnaires' Disease (LD) rarely evolves into pulmonary abscesses. The current systematic review has been designed to explore therapeutical strategies in pulmonary cavitary LD. Methods A research strategy was developed and applied to the databases Embase, Pubmed, and Web of Science from the 1st of January 2000 to the 1st of November 2022. Original articles, case series, case reports, and guidelines written in English, French, German, Italian, and Dutch were considered. Furthermore, medical records of patients treated at the University Hospital UZ Brussel for LD cavitary pneumonia, between the 1st of January 2016 to the 1st of January 2022, were reviewed. Results Two patients were found by the UZ Brussel's medical records investigation. Through the literature review, 23 reports describing 29 patients, and seven guidelines were identified. The overall evidence level was low. Result of synthesis (case reports) The median age was 48 years and 65% were male. A polymicrobial infection was detected in 11 patients (44%) with other aerobic bacteria being the most commonly found. At diagnosis, 52% of patients received combination therapy, and fluoroquinolones were the preferred antimicrobial class. Anaerobic coverage was neglected in 33% of patients. Result of synthesis (guidelines) Three guidelines favor monotherapy with fluoroquinolones or macrolides, while one suggested an antimicrobial combination in case of severe LD. Four guidelines recommended anaerobic coverage in case of lung abscesses. Conclusion To date, the evidence supporting cavitary LD treatment is low. Monotherapy lowers toxicity and might be as effective as combination therapy. Finally, anaerobes should not be neglected. Graphical Abstract